Ingenieros en la sombra: biografía de una idea - Ewen, Stuart (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2008)
We publish in this issue a new chapter of the book of the distinguished American researcher, Stuart Ewen, PR! A Social History of Spin (Basic Books, New York, 1996), whose Spanish translation the author has gave at our journal. In this new issue, witch is a continuation of the published in the first number of Pensar la Publicidad, Ewen pursue its inquiry about how the foundations of the manufacture consent during the period between the two World Wars were layed, focusing specifically on two key figures in the history of that social engineering: Walter Lippmann, and Edward L. Bernays. Stuart Ewen is also author of Captains of Consciousness: Advertising and the Social Roots of the Consumer Society (1977), All Consuming Images: The Politics of Style in Contemporary (1988) and, written in collaboration with Elizabeth Ewen, Channels of Desire: Mass Images and the Shaping of American Consciousness (2th ed. 1992). The second of these books was translated into Spanish with the title Todas las imágenes del consumismo. La política de estilo en la cultura contemporánea (México, Grijalbo, 1991).
Keywords: Manufacture consent; Public opinion; Publicity; Press agent